Efeitos da hidroginástica na pressão arterial sistêmica, em variáveis metabólicas e na composição corporal em mulheres saudáveis com sobrepeso ou obesidade - Borges, Arituza Tosta (2007)
The current study has researched the effects of hidrogymnastic on systemic blood pressure, on metabolic variables as well as on the body structure of healthy women who are overweighted or obese. There have been twenty one volunteers for this study split into two groups: experimental group (n=10, 41,9 + 3,5 years), the ones who joined the hidrogymnastic program and control group (n=11, 43,2 + 3,4 years). All of them had previously sedentary life, were clinically healthy, underwent physical test, had blood test and blood biochemic, all of the above have been considered normal. The following have been excluded: alcoholism, tobaccoism, post menopause, unbalanced menstrual period and the use of medications potentially able to change the variable studied. The hidrogymnastic program lasted thirteen weeks with fifty minutes class, with moderate intensity and repeated three times a week. The groups have been compared to each other before and after the training period, they have compared regarding the systemic blood pressure, plasmatic levels of lipids, fibrinogen, nitrite and cortisol, corporal weight and body mass index. As statistics data the test t for Student, U for Mann-Whitney or Wilcoxon were used considering significant value of p=0,05. At the end of the hidrogymnastic period there was as well decreasing of the systolic pressure in the experimental group. Similar result was noted in the mean blood pressure also found when comparing both group. The diastolic pressure was more elevated at the end of the study in the control group and decreased in the experimental group when comparing both groups. It was also noted significant increasing on the plasmatic levels of fibrinogen in the experimental group. These results show that regular physical aerobic exercise, such as, hidrogymnastic, has an important role on the systemic blood pressure control. The changes found on the fibrinogen deserves special attention and investigation on this special group of individuals.